Application of Remote Sensing and Developed Allometric Models for Estimating Wood Carbon Stocks in a North-Western Miombo Woodland Landscape of Tanzania. (5th June 2014) - Soka, Geofrey; Nzunda, Nanjiva
Abstract : Quantifying ecosystem carbon stocks is vital for understanding the relationship between changes in land use and cover (LULC) and carbon emissions; however, few studies have documented the impacts of carbon cycling on Miombo ecosystems. Here, we estimate the amounts of wood carbon which is stored and lost as a result of LULC changes in Kagoma Forest Reserve (KFR) for the periods between 1988 and 2010 using GIS data, Landsat imagery, and field observations. The land cover was captured on the basis of Landsat 5 TM and Landsat 7 ETM. The amounts of wood carbon stored and lost were estimated based on four previously developed allometric models. Spatial analysis of the Landsat images shows that in the year 1988, woodlands dominated the area by covering 32.66% whereas in the year 2010 the woodlands covered only 7.34% of the total area. The findings of the current study reveal that KFR had undergone notable changes in terms of LULC for the period of 1988–2010. It was estimated that the woodlands in the KFR lost an average of 4409.79 tCyr -1 . In this study, the amount of carbon stocks stored was estimated to be 21457.02 tonnes in tree stem biomass based on the area (1226.12 ha) that was covered by woodlands. We estimated that an average of 17.79 tCh -1 was stored in the Miombo woodlands based on the four models. The efforts to ensure sustainable management of the Miombo ecosystem can contribute to the creation of a considerable carbon sink.